RETRIEVAL OF SURFACE CURRENT FROM HIMAWARI-8 SEA SURFACE TEMPERATURE DATA AND PARTICLE IMAGE VELOCIMETRY METHOD - Wati, Kadek Setiya; Osawa, Takahiro; Astawa Karang, I Wayan Gede (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2023)
As human activity occurs at the surface, which is influenced by surface currents, understanding surface currents is crucial. Ocean currents are not solely caused by wind, but also of other factors, such as sea surface temperature. To obtain surface current data, BMKG used HF radar installed in several places, including Flores Sea. This location is significant because it has large ports and heavy crossing traffic. This study aims to analyse surface current data retrieve from Himawari-8 SST data by applied PIV algorithm. Using the PIV algorithm, a cross-correlation plane is generated by comparing two identically sized interrogation windows obtained from successive images. On 5 December 2022 in the Flores Sea, Himawari-8 SST data was employed to estimate sea surface currents every 10 minutes. Surface current motion varies widely from image to image. Western areas are dominated by westward currents, while central and eastern areas are dominated by eastward currents during daylight hours, and westward currents during the night. Synoptic wind affects surface current movement during those hours. Validation with observational data from the Labuan Bajo HF radar shows that the V component current estimation is better than the U component current estimation. This is particularly prevalent in the south and in areas close to the KAWA radar HF location. Keywords: Flores Sea; SST; Himawari-8; PIV; surface current